(untitled) (Papeles, 2024)
The ecological crisis, a product of climate change, global warming, the loss of biodiversity and environmental pollution, is a problem that is specific to today’s society. In this context, compliance with environmental regulations by the administrators of legal entities (whether they have an economic purpose or not) is substantial in order to prevent environmental damage. In Argentina, the Civil and Commercial Code (CCC) and the special legal microsystems contain provisions on the liability of administrators of private legal entities. On the other hand, environmental law regulates environmental damage, and establishes legal consequences for administrators who generate damage to the environment in the development of their powers. This article aims to identify and analyze the regulations that regulate the responsibility of the administrators of private legal entities and those that protect environmental damage in the field of the Argentine legal system, with the aim of creating some reflections on the importance of that administrators integrate the duty of preserving a healthy, balanced environment, suitable for human development and so that productive activities satisfy present needs without compromising those of future generations.